ASSESSING THE EDUCATIONAL PREFERENCES OF RURAL NIGERIAN POOR IN CROSS RIVER STATE - Betiang, Peter A; Angioha, Catherine U (PEOPLE: International Journal of Social Sciences, 2018)
This study was designed to assess the educational preferences of rural Nigerian poor. Four research questions were formulated to guide the study and the structured interview was used to elicit information on their preferences. Four hundred respondents were purposively drawn from the ten wards of Obudu Local Government Area of Cross River State Nigeria. The responses were coded on a scale of preferred, not preferred to not sure. Data collected was analyzed using simple percentage. Results showed that respondents showed less preference for basic literacy-related programmes, while expressing strong preference for work-oriented functional literacy, vocational education and educational programmes that offered practical skills, recommendations were made on the basis of these findings.